2015
DOI: 10.7314/apjcp.2015.16.12.4863
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathology Figures and Long-term Effects of Tamoxifen Plus Radiation on Survival of Women with Invasive Ductal Carcinoma and Triple Negative Breast Cancer

Abstract: Background: Triple negative breast cancer (TNBC), characterized as estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 Her2 negative and accounting for 10-17% of all breast carcinomas, is only partially responsive to chemotherapy and suffers from a lack of clinically established targeted therapies. The aim of the current study was to evaluate the patterns of treatment and clinicopathology figures in Kurdish patients with triple-negative breast cancer, and to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…The most common causes of breast cancer are genetic factors and also environmental and lifestyle risk factors such as early menarche, late menopause, low parity, giving birth at an advanced age, alcohol consumption, and obesity (Dossus & Benusiglio, ). Nowadays, cancer treatment includes surgery, chemotherapy, radiotherapy, and some other procedures; however, in the advanced stages, chemotherapy is often the only effective method of cancer treatment (Payandeh, Sadeghi, Sadeghi, & Aeinfar, ). Although, in recent years, chemotherapy agents and antiemetic drugs have had significant advancement, chemotherapy‐induced nausea and vomiting (CINV) has remained as one of the worst side effects of cancer therapy (Palatty, Haniadka, Valder, Arora, & Baliga, ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common causes of breast cancer are genetic factors and also environmental and lifestyle risk factors such as early menarche, late menopause, low parity, giving birth at an advanced age, alcohol consumption, and obesity (Dossus & Benusiglio, ). Nowadays, cancer treatment includes surgery, chemotherapy, radiotherapy, and some other procedures; however, in the advanced stages, chemotherapy is often the only effective method of cancer treatment (Payandeh, Sadeghi, Sadeghi, & Aeinfar, ). Although, in recent years, chemotherapy agents and antiemetic drugs have had significant advancement, chemotherapy‐induced nausea and vomiting (CINV) has remained as one of the worst side effects of cancer therapy (Palatty, Haniadka, Valder, Arora, & Baliga, ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] ER positivity predicts response to endocrine therapy such as antiestrogen (tamoxifen) and trastuzumab therapy (herceptin) for tumor with HER2 overexpression. [ 3 ] Ki-67 is a nuclear antigen, which exists in proliferative cells. A number of studies have shown that the immune response of Ki-67 is closely associated with the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…showed that tamoxifen increased the overall survival and disease-free survival rate in ER -/PR + breast cancer patients [79]. In addition, treatment with combination of tamoxifen and radiation increased the overall survival rate and reduced the mortality rate of patients with brain metastasis of triple negative tumors [80]. It is noteworthy that Phase I/II clinical trial for testing e cacy of Tamoxifen and anastrozole on TNBC is currently ongoing (NCT01194908 and NCT01234532).…”
Section: Discussionmentioning
confidence: 99%